The SAGE Handbook of Sport Management 2017
DOI: 10.4135/9781473957961.n30
|View full text |Cite
|
Sign up to set email alerts
|

Sport, the Natural Environment, and Sustainability

Abstract: Given the growing body of research pertaining to sport, the natural environment and sustainability, it is an appropriate time to review the orientation and findings of this work, and to identify further avenues for research. This is especially so given the vast amount of literature published across a range of disciplines that document the evidence of significant change to the natural environment on a global scale. Such environmental issues include the multi-dimensional problem of anthropogenic climate change w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…More studies should quantify the carbon footprint of (inter)national, university sport competitions, and leisure sport practices, particularly in countries that are large emitters of greenhouse gases. Guidelines should be developed to ultimately limit the CO 2 emissions from these sectors and promote sustainable sport management practices (see e.g., [117]). 7.…”
Section: Future Researchmentioning
confidence: 99%
“…More studies should quantify the carbon footprint of (inter)national, university sport competitions, and leisure sport practices, particularly in countries that are large emitters of greenhouse gases. Guidelines should be developed to ultimately limit the CO 2 emissions from these sectors and promote sustainable sport management practices (see e.g., [117]). 7.…”
Section: Future Researchmentioning
confidence: 99%
“…Yet, a revised analysis (Mallen, 2018), using the same parameters as the previous study (Mallen, Stevens and Adams, 2011), identified only 53 additional articles published on the subject in seven years. Dingle (2016) undertook a similar exercise to Mallen (2018) and identified just 51 new articles since 2008. Trendadilova andMcCullough (2018, p.3) published "a rapid review" of literature to determine "if environmental sustainability research addressed the current efforts of the sport sector".…”
Section: Introductionmentioning
confidence: 99%
“…Their study considered journals listed with the North American Society for Sport Management (NASSM) between 2007 and the end of September 2017, finding 84 articles. Compared with Mallen (2018) and Dingle's (2016) analysis this adds n=31 and n=33 publications to the list from an additional two-year period. However, Trendafilova and McCullough (2018, p.10) conclude that "when one looks at the numbers, it is clear that more scholarly work is necessary if we are to keep up with the efforts of the sport sector when it comes to environmental sustainability".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sports environmental research emerged early in the 1980s, but until 2008, only a few occasional and qualitative studies examining the role of the natural environment in the sports context were published (for a review see Mallen et al, 2011). From 2008 onward, the growing public interest in environmental problems was accompanied by proportionally growing research in the field of sports environmental research (Dingle, 2017). While most studies in the early stage tried to answer questions about why and how environmental strategies are applied within sports (e.g., Trendafilova et al, 2013), studies of proenvironmental behavior of spectators and sports participants have attracted the interest of researchers (e.g., McCullough and Cunningham, 2011;Wicker, 2019).…”
Section: Theoretical Framework and Literature Review Sports Environmental Researchmentioning
confidence: 99%